The Influence of Sangkolan Transactions on Wealth Distribution in Madura: A Political Economic Perspective - Alia Fitriyani; Honainah; Tina Syahadatina (Penerbit Hellow Pustaka, 2025)
Madura Island in Indonesia is known for its distinctive culture and unique social and economic dynamics. One of the important traditions in the Madurese socio-economic context is sangkolan, a local practice related to the distribution of wealth within society. The sangkolan tradition has been passed down from generation to generation and still plays an important role in remote villages in Madura. This research aims to analyze the influence of the sangkolan tradition on the distribution of wealth in Madura using a political economic approach. This approach was chosen to understand how local power structures, resource distribution, and socio-economic relations influence wealth distribution patterns among Madurese society. Furthermore, this research explores the role of sangkolan in maintaining the status quo of wealth and power or as a tool for more equitable redistribution. Through political economic analysis, this article reveals how the practice of sangkolan is an important factor in determining wealth distribution patterns in Madura, not only as a symbol of cultural identity, but also as a mechanism that has a real impact on the social and economic structure of society.